Bias‐Free Solar‐Driven Syngas Production: A Fe2O3 Photoanode Featuring Single‐Atom Cobalt Integrated with a Silver‐Palladium Cathode. (7th December 2022) - Zhao, Bin; Huang, Xiaojuan; Ding, Yong; Bi, Yingpu
Abstract: Photoelectrochemical syngas production from aqueous CO2 is a promising technique for carbon capture and utilization. Herein, we demonstrate the efficient and tunable syngas production by integrating a single‐atom cobalt‐catalyst‐decorated α‐Fe2 O3 photoanode with a bimetallic Ag/Pd alloy cathode. A record syngas production activity of 81.9 μmol cm −2 h −1 (CO/H2 ratio: ≈1 : 1) was achieved under artificial sunlight (AM 1.5 G) with an excellent durability. Systematic studies reveal that the Co single atoms effectively extract the holes from Fe2 O3 photoanodes and serve as active sites for promoting oxygen evolution. Simultaneously, the Pd and Ag atoms in bimetallic cathodes selectively adsorb CO2 and protons for facilitating CO production. Further incorporation with a photovoltaic, to allow solar light (>600 nm) to be utilized, yields a bias‐free CO2 reduction device with solar‐to‐CO and solar‐to‐H2 conversion efficiencies up to 1.33 and 1.36 %, respectively. Abstract : Photoelectrochemical reduction of CO2 using a Ag/Pd cathode, integrated with a Fe2 O3 photoanode decorated with single‐atom cobalt, achieves a solar‐to‐syngas conversion efficiency of 2.69 %.